Kajian Yuridis Tindak Pidana Pencucian Uang Yang Berasal Dari Tindak Pidana Korupsi Berdasarkan Peraturan Perundang-Undangan - Timur, Widya; Farozi, Muhammad Alfallah; Jaya, Dwi Putra (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The crime of money laundering (TPPU) is often related to criminal acts of corruption, where the perpetrator tries to disguise the proceeds of the crime so that they appear legitimate in the financial system. This research aims to analyze the legal regulation of money laundering from the proceeds of corruption in Indonesia and evaluate the effectiveness of its implementation, with a case study of corruption in the BAKTI Kominfo BTS 4G project. The method used is normative juridical, with a statutory approach and a case approach. Data is obtained from legal regulations, court decisions, as well as reports from related institutions such as the Corruption Eradication Commission and PPATK. The research results show that although Law no. 8 of 2010 concerning TPPU and Law no. 31 of 1999 jo. UU no. 20 of 2001 concerning Corruption is available, its implementation is still not optimal. The main obstacles include the difficulty of tracking assets, weak coordination between institutions, and sanctions that have not had a deterrent effect. To overcome this, it is necessary to increase supervision of financial transactions, international cooperation in asset recovery, and the use of technology such as Artificial Intelligence (AI) for earlier detection of money laundering.